THE SPIRIT OF DEMOCRACY AS SEEN IN WALT WHITMAN’S "I HEAR AMERICA SINGING" - Tini Mogea; Salaki Reynaldo Joshua (Jurnal Pendidikan dan Sastra Inggris, 2022)
This research is mainly intended to reveal the spirit of democracy in Walt Whitman’s I Hear America Singing. This study is regarded as qualitative research. The data were collected from the main source, the poem itself, and from other books as secondary sources. The data analyzed are presented in descriptive form. The expressive approach and mimetic approach are used to analyze the data. The result of the study shows that Walt Whitman, as the poet lifted up the freedom and competence of the common people to the growth of America. They are mechanics, carpenter, mason, boatmen, deckhand, shoemaker, hatter, wood-cutter, ploughboys, mother, young wife and girl. They have dignity and rights to make full use his/her activities as a part of democracy.